Research on the simulation methods and shock resistance performance of energy absorbing columns in rockburst roadway supports - Dong An; Jinying Fan; Yimin Song; Hailiang Xu (Scientific Reports)
Abstract For the rockburst prevention issue of hydraulic supports in tunnel roadways, a structural design was introduced that adds energy-absorbing components to the hydraulic prop. This anti-shock hydraulic prop can improve the shock resistance of the support by absorbing energy through displacement. A solid-liquid coupling and static-dynamic coupling model for the anti-shock hydraulic prop was established using finite element and SPH particle methods. Impact tests were conducted on the energy-absorbing device and the shock-resistant prop with energy-absorbing columns. Optimization and adjustment of key simulation parameters were performed to achieve long-duration, high-precision simulations of energy-absorbing columns under shock loading in tunnel supports. The synergistic working mechanism between the energy-absorbing device and the hydraulic prop was revealed. The results show that the maximum displacement of the energy-absorbing column was reduced by 25% compared to the ordinary prop. The maximum displacement resistance was reduced by 18% compared to the ordinary prop. The total energy absorption was increased by 80% compared to the ordinary prop. It was found that the energy-absorbing device loaded on the energy-absorbing column could be fully crushed within 13 ms under the impact of a 10.5t hammer. The displacement speed reached 18.5 m/s, with variable stiffness and frequency.